Effect of Single Dose Fenofibrate as an Adjunct to Phototherapy on Unconjugated Neonatal Hyperbilirubinemia: A RCT (Bangladesh Journal of Child Health, 2022)
Background: Fenofibrate is used as an adjunct therapy to reduce bilirubin level and duration of phototherapy. This study was done to determine the efficacy of fenofibrate in the treatment of unconjugated neonatal hyperbilirubinemia.Materials & Method: Total 60 neonates were enrolled and devided into two groups. In group A, a single dose of oral fenofibrate (10mg/kg) was given along with phototherapy, and Group B only phototherapy. Blood samples were collected every 24 hours for total and indirect bilirubin. SGPT was done before and after 24 hours of giving fenofibrate.Result: Baseline serum bilirubin was 16.86± 0.89 in group A and 17.31± 1.19 in group B. After 24 hours of starting phototherapy, the bilirubin level came down to a lower value of 14.83 ± 0.95 mg/dl in group A and 15.73 ± 1.32 mg/dl in group B. After 48 hours it was 12.85 ± 1.06 mg/dl and 14.20 ± 1.24 mg/dl in group A and group B respectively. (P-value 0.004 and 0.001). The mean time needed for phototherapy was 51.20 ± 8.29 hours in group A and 70.40± 6.08 hours in group B (P-value 0.001). The duration was shorter in the fenofibrate group in comparison to the control group. No side effects of fenofibrate were observed after a single dose administration.Conclusion: Administration of a single dose of fenofibrate as an adjunct along with phototherapy to neonates showed a significant reduction of serum bilirubin and duration of phototherapy.BANGLADESH J CHILD HEALTH 2021; VOL 45 (2) : 89-93